All earthly bodies - Mlekoday, Michael, 1985- (Miller Williams poetry series, 2022)
""I am trying to make myself / a thrum of votive light," Michael Mlekoday writes in All Earthly Bodies. "I am trying to let the planet / rename me." Through a kind of lyric dreamwork, Mlekoday sounds the depths-of ancestry and identity, race and gender, earth and self-to track the unbecoming and re-membering of the body"--